Births in Chile: What Has Been the Impact of the Last Wave of Migrant Mothers? [Nacimientos en Chile: ¿Cuál Ha Sido el Impacto de la Última Ola de Madres Migrantes?] - Gutierrez-Pinto, J; Haye-Morales, M; Rubio-Schweizer, G; Gonzalez-Perez, R (Ediciones Doyma, S.L., 2023)
Introduction: Chile has traditionally had a stable process of inmigration of people from Peru, Bolivia and Colombia. In the last eight years, a strong increase of new migrants, mainly from Haiti and Venezuela, commenced. Aim: The aim of this study is to describe the impact this last migratory process has had on births and on the main neonatal demographic and biometric indicators in Chile during the last 8 years. Method: Information from the national database of the Informatics Department of the Chilean Ministry of Health (DEIS), obtained through academic collaboration with the Women s Health Program of the Ministry of Health, was used. All live births that occurred in Chile, during the period between January 2014 and September 2022, were included. Basic perinatal data, prematurity, low birth weight and their relationship with the gestational age of newborns of Chilean, South American and Haitian mothers were evaluated. Results: Births: During the study period, a total of 1,880,754 births occurred in Chile. 8.3% of them (156,858) were of mothers classified as foreigners or migrants in the national civil registry. From 2014 to the present an increase of 316% (3.1 to 12.9%) of births from mothers from other countries has occurred in Chile. The most frequent nationalities of foreign mothers for the period were Perú (23%), Haití (20%), Venezuela (19%), Bolivia (13%) and Colombia (11%). Prematurity: The percentage of births under 37 weeks were similar for Chilean (8.6%) and Haitian (8.6%) mothers and was significantly lower for mothers of other South American nationalities (6.8%), Chi square p < 0.0001 (CI 1.6-1.9). Low birth weight: The percentage of newborns with low birth weight, very low birth weight and extremely low birth weight, was significantly higher for Haitian mothers, when compared to mothers from Chile and other South American countries. Conclusions: Migrant mothers of South American origin have less preterm births and low birth weight babies than Chilean mothers. Haitian mothers had more low birth weight newborns and prematurity at birth than their South American counterparts, however these indicators were better than those published for Haitian mothers in their country of origin. Chilean and South American mothers have similar percentage distribution weight curves according to gestational age; Haitian mothers have lower 10, 50 and 90 percentiles along all the gestational ages studied. Approximately one hundred and fifty thousand girls and boys have been born from migrant women in the last eight years in Chile, posing important challenges for the country s public health services. © 2023